Risk of early death after treatment with curative intent for head and neck squamous cell carcinoma: a retrospective population-based study - Mahmoud Bazina; Rayan Nikkilä; Aaro Haapaniemi; Leif Bäck; Sami Ventelä; Antti Mäkitie (Acta Oncologica)
Background and purpose: Knowledge regarding the risk factors for early death in patients with head and neck squamous cell carcinoma (HNSCC) is scarce. This study aims to evaluate the rate of early death (during or within 6 months of treatment) and its associated risk factors in HNSCC patients treated with curative intent.